(untitled) (Práxis Educativa, 2009)
The purpose of this study was to discuss the development of Mathematics teachers in order to enable them to teach Geometry. The investigation was based on both the professional experience acquired through Math teaching and the Geometry bibliography and teaching, and aimed at investigating the Geometry teaching in Middle School (5th – 8th grade) and the teachers’ background based on the accounts of experienced and less experienced Math teachers and the study cases performed with them. Experienced teachers not only learned Geometry better but also learned different ways to teach it when compared to the less experienced ones. They all accredited their development to their undergraduate program in college and teacher practice, showing that professional growth occurs with time, classroom life, courses, information-exchanging with other teachers and teacher training. Keywords: Teacher training. Teacher knowledge. Mathematics teacher. Geometry teaching.